Is screening of Staghorn Stones cost-effective? - Kavosh, Ali Muhammad; Aminsharifi, Ali Reza; Keshtkar, Vahid; Jafari, Abdosaleh; Abdollahifard, Gholamreza (Urology Journal, 2019)
Background: Staghorn stones can cause damage to the kidneys and are considered as the one of the main cause of renal failure. If they are identified during the initial stages of diagnosis, kidney damage can be prevented. Screening can lead to a better diagnosis. Before the screening, it is necessary to calculate the cost-effectiveness of screening. Methods: Using the possibility calculations of staghorn stones in the society and different age groups as well as a decision tree model, the screening costs and effectiveness were calculated against no screening. Effectiveness was determined based on the number of prevented cases of renal failure. Ultimately, the incremental cost-effectiveness ration (ICER) was calculated and compared with the World Health Organization (WHO) method based on the gross domestic product (GDP) per capita and subgroup analysis was done for different age groups. In addition, the robustness of results was examined by sensitivity analysis. Results: The results of decision tree showed that in the screening group, the expected cost was 8815997 USD and the expected effectiveness was 358 and in the no-screening group, the expected cost was 3954214 USD and the expected effectiveness was 258. Based on the results of the study, screening compared with no screening would increase the cost by 4861783 USD and effectiveness would increase by 100 people. The incremental cost-effectiveness ratio (ICER) showed that for each unit of increase in effectiveness of screening compared with no screening, would lead to an increase the cost by 48618 USD. The results also indicated that screening 30-70-year-old people compared with other age groups (20-70 and 25-70) if done every two years, could reduce the mean costs per preventing each case of renal failure. Conclusion: If screening staghorn stones are done every two years for 30-70-year-old individuals, it would be cost effective considering WHO method and 3026 USD could be saved in the health care system per each person.